Construção, caracterização e perfil biotecnológico do gene xynA2 de Caulobacter crescentus - Jacomini, Débora (2019)
Lignocellulosic residues generated in agroindustrial practices are the most abundant in nature and, currently, there is a world concerning about using them as raw material in the energy production, chemical compounds and food, since they are a great source of renewable organic matter. Biotechnology arises with innovative alternatives, through the enzymes use in the biodegradability of agroindustrial residues. Moreover, enzymes can also be applied in industrial bioprocesses, looking for conventional treatment’s optimization as in the biotreatment of denim. Caulobacter crescentus is a promising bacterium to the biotechnological exploration, due to the presence of seven genes that encode enzymes of xylanolytic complex involved in the lignocellulosic materials metabolism, being five genes of β-xylosidases and two genes of endoxylanases. The objective of this study was to clone, express and characterize biochemically the xynA2 gene, besides testing its xylanolytic action in the hydrolysis of the corn straw residue, and to the denim treatment. The xynA2 was amplified by PCR, cloned into the pUCBM21 cloning vector and subcloned into the pTrcHisA expression vector, which produced a protein with a histidine N-terminal tail. The recombinant xylanase was purified on nickel-sepharose resin, exhibiting a single protein band on the SDS-PAGE gel (43 kDa), with specific activity of 1 U.mg-1. The XynA2 was characterized with optimum alkaline pH (8) and optimum temperature (60 ºC), apart from being considered thermoresistant at 65 ºC and stable at alkaline pH. The C. crescentus enzyme presented predominant activity to the xylan beechwood 1 % substrate, however it does not have celullase function. This substrate specificity allows that the enzyme selectively removes hemicellulose´s components, making industrial processes cleaner and more profitable. Among the tested compounds with xylanolytic activity of XynA2, the DTT was the one that obtained the best result, because it decreased the enzyme´s KM from 21.49 to 5.78 mg.mL-1 and increased the Kcat/KM from 0.12 to 1.63 Us-1, improving the C. crescentus endoxylanase catalytic´s efficiency. Moreover, this enzyme is not inhibited in the presence of moderate concentrations of xylose (50 μmol.ml-1), suggesting that it may act on prolonged hydrolysis reactions since it is not repressed by its final product. XynA2 efficiently hydrolyzed the corn straw by liberating reducing sugars and XOS, that present potential for industrial application. XynA2 acted in jeans treatment, removing the hemicellulose remnants from the fabric, improving its esthetic and commercial properties. According to the literature to date, few xylanolytic alkali enzymes and thermophilic bacterial have been characterized. Therefore, this work contributed strongly to the study of xylanases, which can act in different industrial bioprocesses, such as those in the textile segment and those that use lignocellulosic residues as raw material.